PRILAKU PENGELOLAAN KEUANGAN PENJUAL ES DAWET TERHADAP PENINGKATAN EKONOMI KELUARGA DI KOTA MAKASSAR - Rustan, Rustan (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This study uses a phenomenological approach with a qualitative research design to explore the importance of good financial management for ice dawet sellers in Makassar, who are part of the informal sector and make a significant contribution to the local economy. The research findings indicate that the ability to record and analyze finances, utilize technology, and prepare accurate financial reports greatly assists sellers in accessing formal funding sources. This, in turn, can increase their production capacity and expand their market. With a good understanding and adequate financial training, ice dawet sellers are not only able to manage their income for savings and investment but also to meet other family needs. This enables their businesses to not only survive but also thrive, thereby having a broader positive impact on the well-being of their families and the surrounding community.